Adaptasi Teknologi: Membangun Masyarakat yang Cakap Digital pada Kelurahan Marga Mulya Bekasi - Ramdhania, Khairunnisa Fadhilla; Hasan, Febri Zulfatian; Al Fajriy, Muhamad Fadilah; Pribadi, Janwar Irwansah; Hadi, Muhamad Habib Abfsan Maulana; Hasnandi, Azhar; Mahardika, Fauzan Naufaldy; Heikal, Muhammad Alvien; Al Bari, Naufal; Subakti, Rizky; Saputra, Rues Rizki (Journal Of Computer Science Contributions (JUCOSCO), 2025)
Marga Mulya Subdistrict, despite its considerable potential, faces challenges in achieving sustainable development, one of which is the lack of digital literacy. In particular, the limited understanding of digital security poses a significant challenge, especially in RW 02, where many residents own digital devices but remain vulnerable to risks such as the misuse of personal data and online fraud. Kuliah Kerja Nyata (KKN) conducted by UBHARAJAYA as part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative aims to enhance the digital literacy skills of the local community. This program offers education on the wise, safe, and productive use of digital technology, along with training in the use of applications and social media platforms such as WhatsApp, TikTok, Instagram, and Shopee. Furthermore, the program instills awareness of digital security risks and methods to protect personal information. It is expected that through this initiative, the residents of RW 02 will be able to optimize their use of digital technology and build a smart and resilient digital community.